Reprint of: Connections between single-cell biomechanics and human disease states: gastrointestinal cancer and malaria - Suresh, S.; Spatz, Joachim P.; Micoulet, Alexandre (Acta biomaterialia, 2015)
We investigate connections between single-cell mechanical properties and subcellular structural reorganization from biochemical factors in the context of two distinctly different human diseases: gastrointestinal tumor and malaria. Although the cell lineages and the biochemical links to pathogenesis are vastly different in these two cases, we compare and contrast chemomechanical pathways whereby intracellular structural rearrangements lead to global changes in mechanical deformability of the cell. This single-cell biomechanical response, in turn, seems to mediate cell mobility and thereby facilitates disease progression in situations where the elastic modulus increases or decreases due to membrane or cytoskeleton reorganization. We first present new experiments on elastic response and energy dissipation under repeated tensile loading of epithelial pancreatic cancer cells in force- or displacement-control. Energy dissipation from repeated stretching significantly increases and the cell’s elastic modulus decreases after treatment of Panc-1 pancreatic cancer cells with sphingosylphosphorylcholine (SPC), a bioactive lipid that influences cancer metastasis. When the cell is treated instead with lysophosphatidic acid, which facilitates actin stress fiber formation, neither energy dissipation nor modulus is noticeably affected. Integrating recent studies with our new observations, we ascribe these trends to possible SPC-induced reorganization primarily of keratin network to perinuclear region of cell; the intermediate filament fraction of the cytoskeleton thus appears to dominate deformability of the epithelial cell. Possible consequences of these results to cell mobility and cancer metastasis are postulated. We then turn attention to progressive changes in mechanical properties of the human red blood cell (RBC) infected with the malaria parasite Plasmodium falciparum. We present, for the first time, continuous force-displacement curves obtained from in-vitro deformation of RBC with optical tweezers for different intracellular developmental stages of parasite. The shear modulus of RBC is found to increase up to 10-fold during parasite development, which is a noticeably greater effect than that from prior estimates. By integrating our new experimental results with published literature on deformability of Plasmodium-harbouring RBC, we examine the biochemical conditions mediating increases or decreases in modulus, and their implications for disease progression. Some general perspectives on connections among structure, single-cell mechanical properties and biological responses associated with pathogenic processes are also provided in the context of the two diseases considered in this work.